VIRTUAL GENERAL MEETINGS - Radović, Vuk (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
Traditionally, general meetings have been held as physical meetings. Over the last two decades, legislators have often allowed hybrid meetings, giving shareholders the right to participate both electronically and in person. Since the end of the recent pandemic, we have seen further liberalisation, which means that an increasing number of countries also allow virtual meetings of shareholders. At present, Serbia does not recognise and allow virtual meetings, but it is recommended that this type of meeting should be legally regulated. The purpose of this paper is to define the exact meaning of virtual meetings, to highlight their advantages and disadvantages, to present some selected comparative laws regulating this type of meetings, as well as to analyse some problematic aspects that need to be regulated. The aim of this paper is to give recommendations to the Serbian legislator on the proper way to allow virtual meetings, taking into account all potential problems associated with these meetings.
Keywords: corporation; shareholder meeting; hybrid meeting; virtual meeting; right to participate in the meeting; right to vote; electronic voting